Loneliness as a predictor of Self Harm Tendency in Junior High School Students - Husna, Mai Tiza; Fitri, Rosi Mai; Sudirman, Subhan Ajrin (Proceedings Conference Psychology and Flourishing Humanity, 2026)
This study aims to determine the relationship between loneliness and self-harm tendencies in Junior high school X students in Padang City. The background of this study departs from the phenomenon of increasing self-harm tendencies in adolescents, one of the contributing factors is loneliness. This study uses quantitative methods with a correlational approach. The subjects of this study were 221 students who were selected using random sampling technique. The data collection tools in this study used two scales, namely the Loneliness scale prepared based on Russel's (1996) theory with a reliability of 0.829 and the self-harm tendency scale based on Walsh's (2006) theory with a reliability of 0.843. Data analysis used Spearman correlation Based on the categorization results, it was found that the level of loneliness of SMP X Padang City students was mostly at a moderate level with a percentage of (66.5%), while the level of self-harm tendency was also dominant at a moderate level with a percentage of (51.1%). With a Spearman correlation value of loneliness variables and self-harm tendencies of -0.018 with a significance of 0.795.These results show that there is no relationship between loneliness and the tendency to self-harm in students of Junior high school X in Padang City.